Abnormality and Normality : The Mothering of Thalidomide Children - Roskies, Ethel (Cornell University Press, 2019)
This case study of a highly unusual form of maternity is a valuable addition to the literature on handicapped or deviant children. It is an account of how mothers who took part in a government-sponsored habilitation program in Montreal perceived the process of bearing and rearing (or deciding not to rear) a child with congenital thalidomide-induced deformities. Professor Roskies traces how the biological, psychological, and social factors interacted--and changed over time--as she sought to conceptualize and describe a new way of understanding the elements involved in the mothering of a handicapped child. She raises a number of disturbing questions about our customary ways of viewing this form of mother-child relationship.